y-6=-3(x-4)

Simple and best practice solution for y-6=-3(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-6=-3(x-4) equation:


Simplifying
y + -6 = -3(x + -4)

Reorder the terms:
-6 + y = -3(x + -4)

Reorder the terms:
-6 + y = -3(-4 + x)
-6 + y = (-4 * -3 + x * -3)
-6 + y = (12 + -3x)

Solving
-6 + y = 12 + -3x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + y = 12 + 6 + -3x

Combine like terms: -6 + 6 = 0
0 + y = 12 + 6 + -3x
y = 12 + 6 + -3x

Combine like terms: 12 + 6 = 18
y = 18 + -3x

Simplifying
y = 18 + -3x

See similar equations:

| f(t)=-5t+20t+60 | | 5(-7)-2(-3)= | | -30a-5a= | | -5=-11u | | 3x^2+5xy+y^2-4=0 | | x+9+x= | | Log(x)=3.4 | | 8-6(1-9f)=-30 | | ab=5-5c | | 4r^4-8r^2+16= | | 0.3(3x-12)+11=1+1.5x | | 7x-12=15+4x | | 4r^4-8r^2=16 | | 8x+5=13x-6 | | x(6+10)=58 | | 540-14p=120 | | -2+8+x+(-12)=(-17)+9 | | 6x+11x-25+13x-35+6x+35+8x+15+9x-5+7x+15=900 | | 10x-4+4+4+x-22=0 | | 8-(-3-7x)-2(5x+3)=36 | | n^2+2n-19=5 | | fx+1=9x+4 | | 10(10+8k)= | | 0.6768%= | | f(x+1)=9x+4 | | x^2+-2x+-4=0 | | -6(2n-7)+2(n+4)=-36 | | x-2x-4=0 | | 20(x-0.5)=70 | | 26-18=2(x-2) | | 540-8P=120+6P | | 4(8a+-8)= |

Equations solver categories